Formulasi Sediaan Emulsi Mengandung Astaxanthin dari Ekstrak Minyak Virgin Coconut Oil Cincalok - Indah Aprianti; Siti Nani Nurbaeti; Hadi Kurniawan (Journal Syifa Sciences and Clinical Research, 2022)
Cincalok is a fermented product made from small shrimps and is a traditional food from West Kalimantan, Indonesia. Cincalok fermentation is produced with the composition of sugar and salt and the appropriate fermentation time. Shrimp in general contain several active compounds, one of which is astaxanthin which gives shrimp its red colour. The shrimp fermentation process resulted in an increase in astaxanthin concentrations compared to ordinary shrimp, caused by the breaking of protein bonds in the fermentation process. Virgin coconut oil is used for astaxanthin extraction because of its good solubility in oil. The emulsion formulation was carried out using 2 different non-ionic emulsifiers to see the effect of the emulsifier on the physical dan chemical properties and stability of the emulsion. Emulsifiers used are cremophor RH 40 and tween 80. The evaluation includes organoleptic testing, determination of content, pH, emulsion type, globule size and distribution of globule size, and viscosity. Stability evaluation were also carried out including volume creaming, centrifugation, heating and cooling, and freeze-thaw tests. The results and data showed that the emulsion formula using emulsifier tween 80 was more physically stable than the formula using cremophor RH 40